2019
DOI: 10.1080/21691401.2019.1687501
|View full text |Cite
|
Sign up to set email alerts
|

AuNPs as an important inorganic nanoparticle applied in drug carrier systems

Abstract: Gold nanoparticles (AuNPs), as a kind of inorganic nanoparticle, have been gradually recognized as one of the most promising nanomaterials, which is attributed to their unique optical, electronic, sensing and biochemical characteristics. Due to such unique characteristics, AuNPs have been widely applied in biomedical fields such as diagnosis, biosensing and drug delivery. Except for their use in cancer treatment alone with their photothermal ablation of solid tumours, when used with anticancer drugs, AuNPs can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(80 citation statements)
references
References 166 publications
(189 reference statements)
0
68
0
1
Order By: Relevance
“…currently, there are four types of nanodelivery systems used or in development in oncology: Polymeric, magnetic, metallic and lipid nPs (36). aunPs are non-toxic, can be easily synthesized into different sizes and shapes, have a large surface area to transport drugs, exhibit good biocompatibility and absorb near-infrared light (nir) that can be converted to heat to enable focused thermal therapy (39). aunPs are used in diagnostic imaging, targeted delivery of drugs, radioisotopes and reactive oxygen species-generating enzymes, and plasmonic PTT and photodynamic therapy (40).…”
Section: Development Of Aunps For Antineoplastic Drug Deliverymentioning
confidence: 99%
“…currently, there are four types of nanodelivery systems used or in development in oncology: Polymeric, magnetic, metallic and lipid nPs (36). aunPs are non-toxic, can be easily synthesized into different sizes and shapes, have a large surface area to transport drugs, exhibit good biocompatibility and absorb near-infrared light (nir) that can be converted to heat to enable focused thermal therapy (39). aunPs are used in diagnostic imaging, targeted delivery of drugs, radioisotopes and reactive oxygen species-generating enzymes, and plasmonic PTT and photodynamic therapy (40).…”
Section: Development Of Aunps For Antineoplastic Drug Deliverymentioning
confidence: 99%
“…Among the widely used metallic NPs, gold NPs have several advantages, such as simple preparation method, consistency of size distribution, high permeability through the BBB, easiness of surface functionalization, applicability for various imaging techniques (i.e., magnetic resonance imaging; MRI), and active targeting with external magnetic fields [ 215 , 216 , 217 ]. A recent study demonstrated that neuron-targeted rabies virus glycoprotein (RVG)-bound exosomes-coated gold NPs could be easily transported across the BBB and highly accumulated into the brain in an in vitro BBB model and normal rats [ 218 ].…”
Section: Various Nanocarriers Containing Natural Compounds For Thementioning
confidence: 99%
“…shows the application of Au NPs as a drug carrier under in vivo and their ability to generate ROS with NIR irradiation for the apoptosis of tumor cells. [80]…”
Section: Drug Deliverymentioning
confidence: 99%